Sie wissen das nicht, aber sie tun es - Pikalo, Jernej (Teorija in praksa, 2000)
This article analyses rituals in the U.S. Congress. Congressional rituals are seen as a symptomatic practice that runs contrary to the common-sense perception about rationality of parliaments. It is claimed that rituals, played out on the Hill, are on the one hand contra-productive for integration of the whole American nation, and on the other hand, productive for reproduction of dominant power relations. Rituals are not seen as something negative, but rather as equally important as adopting laws for the Congress and its proceedings.
Keywords: parlamenti; Kongres ZDA; politični obredi; politično komuniciranje; politična antropologija; politična ideologija; United States of America; ZDA